Secure and efficient elliptic curve-based certificate-less authentication scheme for solar-based smart grids - Bari Shovon, Reduanul; Mohammad, Ashif; Das, Rimi; Hossain, Tuhin; Ahasun Habib Ratul, Md; Kundu, Ronjon; Ahsan Arif, Md. (Bulletin of Electrical Engineering and Informatics, 2025)
Solar-based smart grids have emerged as a transformative force, encapsulating a paradigm shift towards decentralized and sustainable power generation. However, this evolution is accompanied by growing concern-authentication challenges that pose a substantial threat to solar-based smart grids' security. Existing work done by researchers reveals a gap in addressing these authentication issues, resulting in vulnerabilities that compromise the overall security and performance of solar enabled smart grid infrastructures. In response to these concerns, this paper suggests a novel certificate-less authentication scheme designed explicitly for solar-based smart grids. Our technique, which uses elliptic curve (EC) encryption, mitigates authentication problems and navigates the resource limits inherent in a smart grid environment. The security evaluation also shows that our mechanism security is higher in terms of the security attributes it delivers. Supported by a Scyther-based protocol specification, our solution undergoes a rigorous security analysis, demonstrating its robustness and effectiveness in critical security attributes. Furthermore, a performance evaluation underscores the efficiency of our scheme, positioning it as a robust, and effective solution for fortifying solar-based smart grid environments against evolving cyber threats.